2015
DOI: 10.1002/chem.201503676
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Transformation of Ethane by Au2VO3+ Clusters with Closed‐Shell Electronic Structures

Abstract: The study of chemical reactions between gold-containing heteronuclear oxide clusters and small molecules can provide molecular level mechanisms to understand the excellent activity of gold supported by metal oxides. While the promotion role of gold in alkane transformation was identified in the clusters with atomic oxygen radicals (O(-.)), the role of gold in the systems without O(-.) is not clear. By employing mass spectrometry and quantum chemistry calculations, the reactivity of Au2 VO3(+) clusters with clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…After confining the cluster ions in the trap for about 0.9 ms, the reactant gas molecules (N 2 ) were delivered through a third pulsed valve to interact with the clusters. It has been demonstrated that the ions were thermalized to room temperature (298 K) before reactions. After interacting for about 7 ms, the reactant and product ions ejected from the LIT were transferred into the TOF-MS for mass and intensity measurements.…”
Section: Methodsmentioning
confidence: 99%
“…After confining the cluster ions in the trap for about 0.9 ms, the reactant gas molecules (N 2 ) were delivered through a third pulsed valve to interact with the clusters. It has been demonstrated that the ions were thermalized to room temperature (298 K) before reactions. After interacting for about 7 ms, the reactant and product ions ejected from the LIT were transferred into the TOF-MS for mass and intensity measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, another isomer 1 IS6 with a closed-shell electronic structure and separate gold atoms was also determined as candidates for the ground-state structures of Au 2 VO 4 + since it has close energy to 3 IS1. The previous study has determined the ground-state structure of Au 2 VO 3 + cluster ( 1 IS4, Figure b), which has a closed-shell electronic structure with two terminal gold atoms and one terminal oxygen atom (O t ). The gold atoms terminally bonded with bridging oxygen atoms are separated from each other.…”
Section: Resultsmentioning
confidence: 99%
“…Density functional theory (DFT) calculations using the Gaussian 09 program were carried out to investigate the mechanistic details of catalytic H 2 oxidation mediated by Au 2 VO x + clusters ( x = 2–4). The TPSS functional has been proved to perform well for the Au–V–O system; , thus, the results by TPSS were given throughout this work. The TZVP basis set for V, O, H atoms and a D95 V basis set combined with the Stuttgart/Dresden relativistic effective core potential (denoted as SDD in Gaussian software) for the Au atom were used in all the calculations.…”
Section: Methodsmentioning
confidence: 99%
“…The DFT calculations with the Gaussian 09 program were employed to study the structures of AuV 2 O 5 + cluster and the reaction mechanism with H 2 . The TPSS functional has been proved to perform well for the Au–V–O system; ,− thus, the results by TPSS were given throughout this work. The TZVP basis set for V, O, H atoms and a D95V basis set combined with the Stuttgart/Dresden relativistic effective core potential (denoted as SDD in Gaussian software) for the Au atom were used in all the calculations.…”
Section: Methodsmentioning
confidence: 99%